2022
DOI: 10.3758/s13415-022-01027-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity with medial temporal regions differs across cultures during post-encoding rest

Abstract: Connectivity of the brain at rest can reflect individual differences and impact behavioral outcomes, including memory. The present study investigated how culture influences functional connectivity with regions of the medial temporal lobe. In this study, 46 Americans and 59 East Asians completed a resting state scan after encoding pictures of objects. To investigate cross-cultural differences in resting state functional connectivity, left parahippocampal gyrus (anterior and posterior regions) and left hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 90 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…These are labeled as "exploratory", and not incorporated into the discussion section. The data were collected as part of a larger project studying cognition and neural activity across cultures [75][76][77]. The sample size was based on estimates needed for the primary fMRI study [76].…”
Section: Analytic Planmentioning
confidence: 99%
“…These are labeled as "exploratory", and not incorporated into the discussion section. The data were collected as part of a larger project studying cognition and neural activity across cultures [75][76][77]. The sample size was based on estimates needed for the primary fMRI study [76].…”
Section: Analytic Planmentioning
confidence: 99%
“…There were 4 runs in the test phase, and each run took about 6 minutes and 31 seconds. 3 Comparison of young adult resting state data across cultures has been published in Zhang et al (2022).…”
Section: Mnemonic Similarity Task (Mst)mentioning
confidence: 99%
“…3Comparison of young adult resting state data across cultures has been published in Zhang et al (2022).…”
mentioning
confidence: 99%
“…Neuroimaging studies have also found distinct patterns of neural activation in people from different cultures (Rule et al, 2013 ; Zhang et al, 2022 ). One study compared brain activity in participants from the United States and Japan in response to affectively laden stimuli and found cultural differences in reward system activity (Freeman et al, 2009 ).…”
Section: Cultural Influences On Brain Functioningmentioning
confidence: 99%